O desenvolvimento da interface cidade-porto em Vitória (ES) do período colonial ao início do século XXI: uma cidade portuária? - Vasconcelos, Flavia Nico (2011)
The general context of this research is the development of the relationship between city and port in the cityports. We work on the points of common interface between the city and the urban port from its historical, economical and physical evolution. The work by Brian Hoyle on the development of port-city interface is used as the main theoretical reference in the port cities. The historical dynamics of the port-city interface in the cityports is marked by phases of approach and retreat, as a result of interests, sometimes converging, sometimes contrasting, with regards to port-urban areas, socioeconomical development and other common issues. In this study we identify these historical moments of approach and retreat between the city and the urban port of Vitoria (ES) since the colonial period (when city and port were born) until the first decade of this century. The conclusion is that the city of Vitoria (ES) was born and raised in close association with its urban port until the mid-twentieth century, when a phase of progressive distancing and growing conflict initiated, only reversed in the first decade of this century. The objective of this research is to identify those different historical moments of approach and retreat at the port-city interface of Vitoria and the variables or aspects that triggered them. By studying each of these moments, we discuss about the city of Vitória (ES): is it a cityport or not? Unlike the beginning, when city and port were part of the same urban logic, the isolated policies by the local government as well as the lack of interest of the civil society lead us to the conclusion that the city of Vitoria (ES) does not see itself as a cityport